CircRNF144B/miR-342-3p/FBXL11 axis reduced autophagy and promoted the progression of ovarian cancer by increasing the ubiquitination of Beclin-1 - Wenting Song; Zhirui Zeng; Yilei Zhang; Haili Li; Huimin Cheng; Jun Wang; Fengrui Wu (Cell Death and Disease, 2022)
Abstract Circular RNAs (circRNAs) can regulate autophagy and ovarian cancer (OC) progression. However, autophagy-associated circRNAs involved in OC progression are largely unknown. Bioinformatics, RNA sequencing, and qRT-PCR were conducted to detect circRNF144B expression in OC as well as its relationship with patient prognosis. Functional experiments were used to determine the effects of circRNF144B on the proliferation, mobility and autophagy of OC. Double luciferase reporter assays, immunoprecipitation, and ubiquitination detection were performed to determine the molecular mechanisms of circRNF144B in autophagy and OC progression. CircRNF144B was elevated in OC tissues with low autophagy levels, and associated with poor prognosis. CircRNF144B promoted the malignant biological properties of OC cells, and inhibited the autophagy. Mechanistically, circRNF144B acts as a sponge for miR-342-3p and inhibits miR-342-3p-induced degradation of lysine demethylase 2 A (FBXL11) mRNA, leading to elevated FBXL11 protein levels. Elevated FBXL11 promoted the ubiquitination and degradation of Beclin-1, thus inhibiting autophagy. In conclusion, CircRNF144B increased FBXL11 level by sponging miR-342-3p, whereas elevated FBXL11 promoted the ubiquitination and protein degradation of Beclin-1, thus suppressing autophagy flux and promoting OC progression. Thus, circRNF144B may be an effective target for OC therapy.